Women Starting Up in the Digital Creative Industries in China - Wang, Qing (Curtin University, 2022)
The pervasive digital technologies and the state’s promotion of “Mass Entrepreneurship and Innovation” have facilitated changes in China’s creative economy. This thesis examines the role and lived experience of women entrepreneurs who set up their own business (i.e., start-ups) in China’s digital creative industries by using in-depth interview, observations and document analysis. This study makes contribution to both the scholarship of gender and creative work, and precarity in creative economy in the context of China.